2022
DOI: 10.1136/jitc-2021-004032
|View full text |Cite
|
Sign up to set email alerts
|

In PD-1+ human colon cancer cells NIVOLUMAB promotes survival and could protect tumor cells from conventional therapies

Abstract: BackgroundColorectal cancer (CRC) is one of the most prevalent and deadly tumors worldwide. The majority of CRC is resistant to anti-programmed cell death-1 (PD-1)-based cancer immunotherapy, with approximately 15% with high-microsatellite instability, high tumor mutation burden, and intratumoral lymphocytic infiltration. Programmed death-ligand 1 (PD-L1)/PD-1 signaling was described in solid tumor cells. In melanoma, liver, and thyroid cancer cells, intrinsic PD-1 signaling activates oncogenic functions, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…Quiescent cancer cells resist T‐cell attack by forming an immunosuppressive niche in primary breast cancer 53 . A very recent total RNA‐seq study revealed that in PD‐1+ human colon cancer cells, tumor survival pathways activation and up‐regulation of DCAF13 expression were observed after being treated with anti‐PD‐1 nivolumab (NIVO), suggesting DCAF13 may affect the patient's response to immune checkpoint suppression therapy as an immunosuppressor in colon cancer 54 . Our findings suggest that targeting DCAF13 inhibition may be a possibility to alter the immune microenvironment and enhance immunotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Quiescent cancer cells resist T‐cell attack by forming an immunosuppressive niche in primary breast cancer 53 . A very recent total RNA‐seq study revealed that in PD‐1+ human colon cancer cells, tumor survival pathways activation and up‐regulation of DCAF13 expression were observed after being treated with anti‐PD‐1 nivolumab (NIVO), suggesting DCAF13 may affect the patient's response to immune checkpoint suppression therapy as an immunosuppressor in colon cancer 54 . Our findings suggest that targeting DCAF13 inhibition may be a possibility to alter the immune microenvironment and enhance immunotherapeutic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ICIs targeting PD-1, PD-L1, or CTLA4 have enabled the possibility of long-term survival in patients with tumors such as melanoma, HCC, breast cancer, and colorectal cancer ( 47 , 48 ). Previous studies demonstrated that tumor cell-intrinsic ICGs regulated tumor development ( 34 , 49 , 50 ). Therefore, correlations between CRGs and ICGs at the mRNA level were investigated and discussed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The patients with high-risk scores might be more sensitive to ICIs responses and Elesclomol, Indoximod, nivolumab and Pazopanib had a treatment advantage in the high-risk group. ICIs can effectively treat advanced MSI-H tumors and MSI-H can be used as a biomarker for treatment ( 55 ). The present study hypothesized that the proportion of patients with MSI-H was higher in the high-risk group.…”
Section: Discussionmentioning
confidence: 99%